Pharmacology - Dass, Sujata K.; Singh, Mukul (New Delhi : Shree Publishers & Distributors, 2009)
The book has been designed to serve as an introductory manual on the field of pharmacology. Pharmacology began as an experimental science in the 19 century with the work of Francois Magendie, who studied the mechanism of absorption and distribution of drugs in the human body and their localization at the site of their action. Today, as the knowledge of the human body continuously increases, the field of pharmacology has also changed substantially. It has become possible, through molecular analysis of receptors, to design chemicals that act on specific cellular signaling or metabolic pathways by affecting sites directly on cell-surface receptors. This book undertakes a deep exploration of the field beginning from the history and development of the science to its current trends and developments, as well as what it entails. The thrust is on acquainting the readers with the researches and experiments being carried out in the field, and how they are affecting the field of pharmaceuticals. It also comprehensively addresses the basic principles of pharmacology, providing informative case reports and illustrations. The text is sectioned off into complete blocks of knowledge, ranging from drugs acting on synaptic and neuroeffector sites to selected aspects of therapeutics. It is hoped that the comprehensive and informative nature of the book renders itself as a useful and resourceful text for pharmacology students.
Preface -- Chapter 1. general pharmacology -- Chapter 2. pharmacology of peripheral nervous systems -- Chapter 3. pharmacology of central nervous system -- Chapter 4. pharmacology of cardiovascular system -- Chapter 5. drugs acting on Hemopoietic system -- Chapter 6. drugs acting on reproductive and urinary systems -- Chapter 7. autacoids -- Chapter 8. drugs acting on respiratory system -- Chapter 9. drugs acting on gastrointestinal tract -- Chapter 10. pharmacology of endocrine system -- Chapter 11. chemotherapy -- Chapter 12. pharmacology of immune system -- Chapter 13. pharmacology of the eye -- Chapter 14. principles of toxicology -- bibliography -- index.
includes bibliographical references and index
Keywords: Pharmacology; Drugs; Chemotherapy